Transfer of photosynthetic NADP+/NADPH recycling activity to a porous metal oxide for highly specific, electrochemically-driven organic synthesis - Siritanaratkul, B; Megarity, C; Roberts, T; Samuels, T; Winkler, M; Warner, J; Happe, T; Armstrong, F (Royal Society of Chemistry, 2017)
In a discovery of the transfer of chloroplast biosynthesis activity to an inorganic material, ferredoxin-NADP+ reductase (FNR), the pivotal redox flavoenzyme of photosynthetic CO2 assimilation, binds tightly within the pores of indium tin oxide (ITO) to produce an electrode for direct studies of the redox chemistry of the FAD active site, and fast, reversible and diffusion-controlled interconversion of NADP+ and NADPH in solution. The dynamic electrochemical properties of FNR and NADP(H) are thus revealed in a special way that enables facile coupling of selective, enzyme-catalysed organic synthesis to a controllable power source, as demonstrated by efficient synthesis of l-glutamate from 2-oxoglutarate and NH4+.